Hukum Perkawinan Sirri yang ditinjau dalam beberapa Aspek (Yuridis, Administrasi Kependudukan, Maslahah Mursalah) - El Khair, Rozien Mohammad; Sitorus, Iwan Ramadhan; Suryani, Suryani (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2025)
Abstract: Currently, many marriages are conducted solely based on religious law or personal beliefs without involving government officials, and therefore are not legally recognized by the state. In Indonesia, marriages must comply with two inseparable regulations: religious law and state law. Marriage registration is not only an administrative requirement but also a means to ensure social order and public welfare. If a marriage is valid according to religion but not registered with the Office of Religious Affairs (KUA) or an authorized official, it is not legally valid in the eyes of the state. This study aims to answer three main questions: (1) the impact of unregistered (sirri) marriages on population administration, (2) the inhibiting factors in the juridical review of sirri marriages from the perspective of maslahah al-mursalah, and (3) the role and effectiveness of government institutions in implementing marriage registration laws and their influence on societal practices. The research uses a library study approach with a statutory method. The findings show that sirri marriages are valid under Islamic law but do not meet the formal legal requirements of the state, and therefore are not recognized and do not produce legally protected consequences due to the absence of authentic proof of marriage.Keywords: Sirri Marriage, Juridical, Population Administration, Maslahah Al-Mursalah.Abstrak: Saat ini, banyak pernikahan dilakukan hanya berdasarkan hukum agama atau kepercayaan pribadi tanpa melibatkan pejabat pemerintah, sehingga tidak diakui secara hukum negara. Di Indonesia, pernikahan harus memenuhi dua regulasi yang tidak terpisahkan: hukum agama dan hukum negara. Pencatatan pernikahan bukan hanya persyaratan administratif, tetapi juga sarana untuk menjaga ketertiban sosial dan kemaslahatan bersama. Jika pernikahan sah menurut agama tetapi tidak dicatat di Kantor Urusan Agama (KUA) atau oleh pejabat berwenang, maka tidak sah secara hukum negara. Penelitian ini bertujuan menjawab tiga pertanyaan utama: (1) Dampak nikah siri terhadap administrasi kependudukan, (2) Faktor penghambat kajian yuridis nikah siri dari perspektif maslahah al-mursalah, dan (3) Peran dan efektivitas lembaga pemerintah dalam pelaksanaan pencatatan nikah siri serta pengaruhnya terhadap praktik masyarakat. Metode penelitian menggunakan studi pustaka dengan pendekatan perundang-undangan. Hasil penelitian menunjukkan bahwa nikah siri sah menurut hukum Islam, tetapi tidak memenuhi persyaratan formal hukum negara sehingga tidak diakui dan tidak menimbulkan akibat hukum yang dilindungi negara akibat tidak adanya bukti otentik perkawinan.Kata Kunci: Perkawinan Sirri, Yuridis, Administrasi Kependudukan, Maslahah Al-Mursalah.